2011
DOI: 10.7439/ijbar.v2i7.37
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Rectal Temperature and Body Weight of Rat Against Typhoid

Abstract: Typhoid fever (TF) is an important communicable disease in many developing countries. Salmonella, a gram negative bacilli, and can survive during certain stages of host parasite interaction. Nitric oxide (NO) is a versatile molecule produced in a biological system;previous studies have suggested that exogenous administration of L -arginine results in increased NO production, indicating that endogenous substrate is insufficient for maximal NO production. Taking these facts in to consideration, it was thought pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…from northeast Queensland is widespread in this area and southwards to northeastern New South Wales and grows as small trees to 20 m high . The genus Alangium is the source of over 200 characterized natural products, consisting of numerous benzoquinolizidine and tetrahydroisoquinoline-monoterpene alkaloids, terpenoids, and simple aromatic structural classes, that have been reported with diverse biological activities including antioxidant, , antimicrobial, antifertility, antiarthritic, antidiabetic, , antibacterial, , anticancer, antifungal, DNA damaging, , and dihydrofolate reductase inhibition activity . It is reported that the root extract of Alangium villosum has anti-inflammatory activity .…”
mentioning
confidence: 99%
“…from northeast Queensland is widespread in this area and southwards to northeastern New South Wales and grows as small trees to 20 m high . The genus Alangium is the source of over 200 characterized natural products, consisting of numerous benzoquinolizidine and tetrahydroisoquinoline-monoterpene alkaloids, terpenoids, and simple aromatic structural classes, that have been reported with diverse biological activities including antioxidant, , antimicrobial, antifertility, antiarthritic, antidiabetic, , antibacterial, , anticancer, antifungal, DNA damaging, , and dihydrofolate reductase inhibition activity . It is reported that the root extract of Alangium villosum has anti-inflammatory activity .…”
mentioning
confidence: 99%